Ukrainian Diaspora literature for children and youth as the subject of the theoretical and critical research (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
This paper represents the series of publications devoted to the Ukrainian Diaspora literature for children and youth. It focuses on studying critical materials and theoretical works that cover the categories of “literature for children” and related literary problems, as well as the actual issues of literature for children and youth of Ukrainian Diaspora writers.The paper notes that the comprehension of the literature for children and youth should be investigated in the following priority ways: theoretical ones considering and formalizing the categories and definitions, in particular, “literature for children” and “literature for children and youth”, tasks and functions of “literature for children”, its period classification; historical and literary and typological ones, covering the actual consideration of works written for this reader group.The article deals with the Ukrainian Diaspora literature for children and youth, which has not been the subject of a thorough study. Present-day research studying the Ukrainian Diaspora heritage can be divided into several groups: biographical papers, analyzing the works of writers for the “adult” reader, in particular E. Andiievska, Ivan Bagrianyi, V. Vynnychenko, Vera Vovk, I. Kachurovskyi, B. Lepkyi, L. Mosendza, S. Cherkasenko; critical works studying the literature for children written by emigrant writers, which include reviews of books, book prefaces, work interpretations, life and work reviews. Textbooks in literature for children take a special place in the contemporary literary discourse. They represent the “child” works of the Ukrainian Diaspora writers. The analysis of these works gives the following observations: on the one hand, the Ukrainian literature for children and youth can take its own special place in the Ukrainian literature, on the other hand, the Ukrainian Diaspora literature for children and youth is the discovery of the Other Ukraine different from the mainland Ukraine.Studying the research papers on the issues of the Diaspora literature for children allows tracing the formation of critical thinking among the Ukrainian Diaspora writers. In particular, the categories “literature for children” and “literature for children and youth” are defined as synonymous. This concept includes understanding of literature for children as the literature actually FOR children, ABOUT children, and even ON BEHALF of the little reader (Leonid Poltava).The attention of the Ukrainian Diaspora critique researchers is mostly paid on the problems of period classification of the literature for children, which is presented in integrity with mainland Ukrainian literature for children and youth, though it is carried out abroad. Thus, the writers consider the Diaspora literature for children written in emigration and literature for children written in Ukraine as the whole literary process. Critics try to demonstrate both the continuity of its development, its connection with the native land and the contrast of ideology and values.The article also emphasizes the heterogeneity of literature for children and youth. The Ukrainian Diaspora critics (B. Goshovskyi, R. Zavadovych, L. Khraplyva-Shchur) determine the following periods: pre-school books, school books and books for adolescents and youth. This division is constructed to the idea of the continuation implemented by the theorists of the Ukrainian Diaspora literature for children.The peculiarities of the children’s books for different age groups are the subject of consideration in popular reviews of that time. They are often published on the pages of the journal “Our Life”. The following structure is typical for them: the definition of an age group, the disclosure of the characters, defying the issues, the assessing of artistic design and illustrations of the book.Among the problem topics in the research papers on the Diaspora literature for children are the following: the functions and role of this literature, which is meant to preserve the national and cultural component of Ukrainians.The conclusions emphasize that the study of the Ukrainian Diaspora literature for children and youth can be implemented in several aspects: the comprehension of modern Ukrainian Diaspora literature for children; typological survey and as the part of the native land literature.
Keywords: literature for children and youth; Ukrainian Diaspora; literary studies